2016
DOI: 10.1007/978-1-4939-3609-0_20
|View full text |Cite
|
Sign up to set email alerts
|

The Use of In Silico Models Within a Large Pharmaceutical Company

Abstract: The present contribution describes how in silico models are applied at different stages of the drug discovery process in the pharmaceutical industry. A thorough description of the most relevant computational methods and tools is given along with an in-depth evaluation of their performance in the context of potential genotoxic impurities assessment.The challenges of predicting the outcome of highly complex studies are discussed followed by considerations on how novel ways to manage, store, share and analyze dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Leadscope Model Applier and CASE Ultra include both methodologies. All of the most relevant and widely used in silico systems have been evaluated in extensive validation exercises. , Derek Nexus is a knowledge-based expert system, which applies structural alerts (SAs) and expert knowledge rules (derived from both public and proprietary data by scientists at Lhasa Ltd.) for a wide range of toxicological end points, to predict the toxicity of chemical entities. Sarah Nexus is a QSAR system that utilizes a self-organizing hypothesis network (SOHN) model to generate predictions for mutagenicity.…”
Section: Risk Assessment Approach Based On the “Aware–avoid–assess” P...mentioning
confidence: 99%
See 1 more Smart Citation
“…Leadscope Model Applier and CASE Ultra include both methodologies. All of the most relevant and widely used in silico systems have been evaluated in extensive validation exercises. , Derek Nexus is a knowledge-based expert system, which applies structural alerts (SAs) and expert knowledge rules (derived from both public and proprietary data by scientists at Lhasa Ltd.) for a wide range of toxicological end points, to predict the toxicity of chemical entities. Sarah Nexus is a QSAR system that utilizes a self-organizing hypothesis network (SOHN) model to generate predictions for mutagenicity.…”
Section: Risk Assessment Approach Based On the “Aware–avoid–assess” P...mentioning
confidence: 99%
“…Brigo and Muster showed that the use of two in silico systems in combination, one knowledge- and one statistic-based system, significantly increased the sensitivity toward experimental Ames test data sets . The performance was satisfactory for numerous chemical classes, such as alkyl chlorides, azides, nitro-aromatic compounds, and others.…”
Section: Risk Assessment Approach Based On the “Aware–avoid–assess” P...mentioning
confidence: 99%